Deregulated methionine adenosyltransferase α1, c‐Myc, and Maf proteins together promote cholangiocarcinoma growth in mice and humans‡. Issue 2 (28th April 2016) - Yang, Heping; Liu, Ting; Wang, Jiaohong; Li, Tony W.H.; Fan, Wei; Peng, Hui; Krishnan, Anuradha; Gores, Gregory J.; Mato, Jose M.; Lu, Shelly C.
Abstract : c‐Myc induction drives cholestatic liver injury and cholangiocarcinoma (CCA) in mice, and induction of Maf proteins (MafG and c‐Maf) contributes to cholestatic liver injury, whereas S‐adenosylmethionine (SAMe) administration is protective. Here, we determined whether there is interplay between c‐Myc, Maf proteins, and methionine adenosyltransferase α1 (MATα1), which is responsible for SAMe biosynthesis in the liver. We used bile duct ligation (BDL) and lithocholic acid (LCA) treatment in mice as chronic cholestasis models, a murine CCA model, human CCA cell lines KMCH and Huh‐28, human liver cancer HepG2, and human CCA specimens to study gene and protein expression, protein‐protein interactions, molecular mechanisms, and functional outcomes. We found that c‐Myc, MATα1 (encoded by MAT1A), MafG, and c‐Maf interact with one another directly. MAT1A expression fell in hepatocytes and bile duct epithelial cells during chronic cholestasis and in murine and human CCA. The opposite occurred with c‐Myc, MafG, and c‐Maf expression. MATα1 interacts mainly with Mnt in normal liver, but this switches to c‐Maf, MafG, and c‐Myc in cholestatic livers and CCA. Promoter regions of these genes have E‐boxes that are bound by MATα1 and Mnt in normal liver and benign bile duct epithelial cells that switched to c‐Myc, c‐Maf, and MafG in cholestasis and CCA cells. E‐box positively regulates c‐Myc, MafG, and c‐Maf, but it negatively regulates MAT1A. MATα1 represses, whereas c‐Myc, MafG, and c‐Maf enhance, E‐box‐driven promoter activity. Knocking down MAT1A or overexpressing MafG or c‐Maf enhanced CCA growth and invasion in vivo . Conclusion: There is a novel interplay between MATα1, c‐Myc, and Maf proteins, and their deregulation during chronic cholestasis may facilitate CCA oncogenesis. (Hepatology 2016;64:439‐455)